Effects of Isolated Hyperinsulinaemia on Sensory Function in Healthy Adults - Søfteland, E.; Dimcevski, G.; Graversen, C.; Nedrebø, B. G.; Drewes, A. M.; Frøkjær, J. B. (Experimental and Clinical Endocrinology & Diabetes, 2011)
Gastrointestinal symptoms such as pain, bloating, nausea and vomiting are more frequent in pre-diabetic states as well as established diabetes, compared to healthy individuals. The mechanisms behind these symptoms are multi-factorial and complex. Furthermore, the effect of isolated hyperinsulinaemia on visceral and peripheral sensory function is poorly understood. Thus, the current study aimed to evaluate effects of acute hyperinsulinaemia on sensory function in healthy adults.The sensitivity to electrical oesophageal and median nerve stimulation was assessed in 15 healthy volunteers together with recording of evoked brain potentials. All subjects were studied both fasting and using a euglycaemic hyperinsulinaemic clamp.There was on average a 15% increased sensitivity to oesophageal electrical stimulation during hyperinsulinaemia compared to fasting state (P<0.05), but the sensation after median nerve stimulation remained stable (P=0.58). No significant changes in latencies and amplitudes of evoked brain potentials were observed after oesophageal or median nerve stimulation (all P>0.05).This study suggests that acute isolated hyperinsulinaemia increases visceral sensitivity, but does not influence the somatic sensory function. The lack of changes in the evoked brain potentials may indicate that hyperinsulinaemia affects the visceral sensory system at a peripheral level. Our result suggests distinct functions of insulin in the various parts of the nervous system, and yields further clues to the significance of insulin as a satiety signal.
Keywords: hyperinsulinaemia; experimental pain; oesophagus; median nerve; evoked brain potentials